ChemInform Abstract: From Heteroaromatic Acids and Imines to Azaspirocycles: Stereoselective Synthesis and 3D Shape Analysis. Issue 39 (September 2016) - Chambers, Sarah J.; Coulthard, Graeme; Unsworth, William P.; O'Brien, Peter; Taylor, Richard J. K.
Abstract: Starting from acetic acid substituted indole, azaindole as well as pyrrole derivatives and cyclic as well as acyclic imines a broad range of spiropolycycles is prepared.